IMPLEMENTATION OF THE MERGER CLAUSE BASED ON UNIDROIT PRINCIPLES OF INTERNATIONAL COMMERCIAL CONTRACTS (UNIDROIT Principles) - Fernanda Buan, Fara Carisa (Transnational Business Law Journal, 2022)
In the current era of globalization, there are a significant number of international transactions which require international commercial contracts. The increasing number of international commercial contracts has led to the development of international legal instruments that regulate these contracts and accommodate the needs of the parties involved in international business transactions. One of these instruments is known as the UNIDROIT Principles. A merger provision is typically written into a large number of contracts. This clause is governed by the UNIDROIT Principles, which can be found in one of its provisions. This research paper will analyse the implementation of the merger clause in the UNIDROIT Principles by courts and arbitration. Taking into account the fact that only a few cases have been decided relating to merger clause under UNIDROIT Principles, this research paper will discuss this topic. This paper aims to examine the implementation of merger clauses under UNIDROIT Principles by court and arbitration through the review of related cases. The method used in this study is normative juridical with a descriptive-analytical nature. To date, the judicial and arbitral decisions that are accessible shed light on the meaning of the merger clause and its relation to the interpretation of the contract.